Managing a Global Workforce - Vance (M.E. Sharpe, 2012)
This comprehensive text provides balanced and contemporary coverage of human resource management in the international marketplace. Directed at future general managers and international executives, rather than HR specialists, it is designed to help students as well as professionals recognize the critical human resource issues underlying the cultural and economic challenges they face.